2016
DOI: 10.1097/mcg.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Assessing Medical Treatment for Rectovaginal and Enterovesical Fistulae in Crohn’s Disease

Abstract: Medical therapy, alone or in combination with surgery, appears to benefit some patients with rectovaginal or enterovesical fistula. However, given the small size and low quality of the published studies, it is still difficult to draw conclusions regarding treatment. Larger, better quality studies are required to assess response to medical treatment and evaluate indications for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 70 publications
4
37
1
4
Order By: Relevance
“…It is noteworthy that our rate of complete clinical fistula closure (40%) is similar to that reported in a recent meta‐analysis (41%) . In the post hoc study of ACCENT II, among responders after induction regimen, 45.5% (5 of 11) of fistulas were closed in the infliximab maintenance group .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is noteworthy that our rate of complete clinical fistula closure (40%) is similar to that reported in a recent meta‐analysis (41%) . In the post hoc study of ACCENT II, among responders after induction regimen, 45.5% (5 of 11) of fistulas were closed in the infliximab maintenance group .…”
Section: Discussionsupporting
confidence: 88%
“…Thus, when one of these surgeries could be associated with an anti‐TNF agent, probability of fistula closure was two times higher than when medical treatment was used alone. This rate was higher than what was seen in the study by Kaimakliotis et al, who reported a 44.2% rate of complete response, probably because we did not consider seton drainage as a complementary surgery . However, this rate was similar to studies involving a majority of patients treated with both medical therapy and a complementary surgery .…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Commonly, the CD has a deteriorating course which can make patients' symptoms varied over time. [123] During recent years, CD incidence has raised up globally, and now, it is around 12.7/100,000 and 20.2./100,000 person-years in Europe and North America, respectively. Although CD can involve pediatrics and adults, it mainly affects adolescents and young adults.…”
Section: Introductionmentioning
confidence: 99%